Carcass and Muscle Distribution of Male Kacang Goat from Intensive Fattening with Different Initial Weight - M. Hatta; S. Baco; B. Wello (Jurnal Ilmu dan Teknologi Peternakan, 2015)
Kacang Goat is one of Indonesian native livestock having high potency of production that have to be preserved, especially in South Sulawesi. The purpose of this study was to evaluate carcass percentage of commercial cuts as well as muscle distribution of male kacang goat under intensive fattening system with different initial body weight. Twenty one male of kacang goats were randomly divided into three groups according to their initial body weight. The experiment was carried out according to completely randomized design consisted of three treatments (age group) and seven replications for each treatment. The animals were reared under intensive fattening system for three months. At the initial period of the experiment, each goat was weighed to obtained the initial body weight. At the end of the experimental period, each animal was weighed to obtain the slaughtered weight of each animal. Following the slaughter, carcass processing was performed for each animal. The carcass and carcass cuts then were weighed. The results of study showed that animals having a heavier initial body weight grew faster, had higher carcass percentage, and had lower non carcass percentage.The growth of male kacang goat muscle was evenly distributed.